Clinical Essays in Obstetrics and Gynaecology for MRCOG Part II - (And Other Postgraduate Exams) - Sharma Seema, Arora Mala; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2011)
Keeping in mind the changed format of the MRCOG examination, the author modified and updated the presentation of essays to make it more reader friendly. Beside MRCOG, postgraduate students appearing for Diploma, National board and MD examinations may find it useful. Important points for the general understanding, MCQs and EMQs have been incorporated at the end of each essay and all possible care has been taken to verify the accuracy of course content.
Keywords: MCQs and Self-assessment,Obstetrics and Gynecology; Electronic books